2019
DOI: 10.3791/60309
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of <em>Drosophila melanogaster</em> Flight Muscles for Omics Approaches

Abstract: Drosophila flight muscle is a powerful model to study diverse processes such as transcriptional regulation, alternative splicing, metabolism, and mechanobiology, which all influence muscle development and myofibrillogenesis. Omics data, such as those generated by mass spectrometry or deep sequencing, can provide important mechanistic insights into these biological processes. For such approaches, it is beneficial to analyze tissue-specific samples to increase both selectivity and specificity of the omics finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…To place the eMIC splicing program within the broader AS landscape of Drosophila , we reanalysed published transcriptomic datasets 38 (Table S1) using vast-tools , and searched for AS exons with tissue-level regulation. Similar to previous reports 42, 48, 49 , we found that neural samples showed the highest prevalence of both tissue-enriched and -depleted exons (Supp. Figure 4E).…”
Section: Resultssupporting
confidence: 92%
“…To place the eMIC splicing program within the broader AS landscape of Drosophila , we reanalysed published transcriptomic datasets 38 (Table S1) using vast-tools , and searched for AS exons with tissue-level regulation. Similar to previous reports 42, 48, 49 , we found that neural samples showed the highest prevalence of both tissue-enriched and -depleted exons (Supp. Figure 4E).…”
Section: Resultssupporting
confidence: 92%
“…Lasp (human ortholog LASP1), is the only nebulin family gene in Drosophila, and shown to modify sarcomere and thin filament length, and myofibril diameter [88]. We also identified bruno 1 (bru1 or aret; human homolog CLEF1 and CLEF2), a transcription factor that controls alternative splicing of myofibrils in the IFM [9,89], among other developmental processes. bru1…”
Section: Variation In Gene Regulation Drives Variation In Flight Perfmentioning
confidence: 94%
“…Annotations and unreferenced descriptors of genes' functions, expression profiles, and orthologs were gathered from autogenerated summaries on FlyBase [34,35]. These summaries and descriptors were compiled from data supplied by the Gene Ontology Consortium [36,37], the Berkeley Drosophila Genome Project [38], FlyAtlas [39], The Alliance of Genome Resources Consortium [40], modENCODE [34], PAINT [41], the DRSC Integrative Ortholog Prediction Tool (DIOPT) [42], and several transcriptomics and proteomic datasets [9,12,39,[43][44][45][46]. threshold (gray line).…”
Section: Association Of Additive Snps With Flight Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Genes in the network are connected by edges representing various interaction types (gene-gene, protein-protein, epistatic, etc.). In the case of flight performance, for example, central genes like Wingless [8] and Act88F [9] are essential for wing and indirect flight muscle development, respectively, while peripheral genes would have more subtle effects on flight from systems like metabolism [10], muscle function [11], neuronal function [12,13], and anatomical development [14,15]. Peripheral genes are less likely to experience the same degree of purifying selection as central genes, meaning they are more likely to harbor natural variants that can have subtle effects on phenotype.…”
Section: Introductionmentioning
confidence: 99%